A tailored series of engineered yeasts for the cell-dependent treatment of inflammatory bowel disease by rational butyrate supplementation - Jiahao Wu; He Huang; Lina Wang; Mengxue Gao; Shuxian Meng; Shaolan Zou; Yuanhang Feng; Zeling Feng; Zhixin Zhu; Xiaocang Cao; Bingzhi Li; Guangbo Kang (Gut Microbes, 2024)
ABSTRACTIntestinal microbiota dysbiosis and metabolic disruption are considered essential characteristics in inflammatory bowel disorders (IBD). Reasonable butyrate supplementation can help patients regulate intestinal flora structure and promote mucosal repair. Here, to restore microbiota homeostasis and butyrate levels in the patient’s intestines, we modified the genome of Saccharomyces cerevisiae to produce butyrate. We precisely regulated the relevant metabolic pathways to enable the yeast to produce sufficient butyrate in the intestine with uneven oxygen distribution. A series of engineered strains with different butyrate synthesis abilities was constructed to meet the needs of different patients, and the strongest can reach 1.8 g/L title of butyrate. Next, this series of strains was used to co-cultivate with gut microbiota collected from patients with mild-to-moderate ulcerative colitis. After receiving treatment with engineered strains, the gut microbiota and the butyrate content have been regulated to varying degrees depending on the synthetic ability of the strain. The abundance of probiotics such as Bifidobacterium and Lactobacillus increased, while the abundance of harmful bacteria like Candidatus Bacilloplasma decreased. Meanwhile, the series of butyrate-producing yeast significantly improved trinitrobenzene sulfonic acid (TNBS)-induced colitis in mice by restoring butyrate content. Among the series of engineered yeasts, the strain with the second-highest butyrate synthesis ability showed the most significant regulatory and the best therapeutic effect on the gut microbiota from IBD patients and the colitis mouse model. This study confirmed the existence of a therapeutic window for IBD treatment by supplementing butyrate, and it is necessary to restore butyrate levels according to the actual situation of patients to restore intestinal flora.